Paradoxical Coronary Artery Embolism - A Rare Cause of Myocardial Infarction - Hakim, Fayaz A. (Heart Views, 2014)
Paradoxical coronary artery embolism is a rare, but often an underdiagnosed cause of acute myocardial infarction. It should be considered in patient who presents with chest pain and otherwise having a low risk profile for atherosclerosis coronary artery disease. We describe a case of paradoxical coronary artery embolism causing ST segment elevation myocardial infarction in a patient with upper extremity venous thrombosis. Echocardiography demonstrated a patent foramen ovale (PFO) with bidirectional shunt. In addition to treatment of acute coronary event closure of the PFO should be considered to prevent a recurrence.